2021
DOI: 10.1029/2020gb006651
|View full text |Cite
|
Sign up to set email alerts
|

Summertime Evolution of Net Community Production and CO2 Flux in the Western Arctic Ocean

Abstract: The Arctic Ocean is currently experiencing rapid environmental and ecological changes in response to climate change. In recent decades, sea ice extent has drastically declined, resulting in earlier seasonal ice retreat and thinning (Onarheim et al., 2018; Stroeve et al., 2018). This change has profound and potentially cascading effects, as sea-ice state is a crucial factor to regulate light availability, water column stability and nutrient availability (Taylor et al., 2013). In addition, sea ice provides habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 73 publications
0
26
1
Order By: Relevance
“…Furthermore, summer stratification strengthens its oligotrophic characteristics (Ardyna & Arrigo, 2020; Ji et al., 2019). Interestingly, a recent study further found that NCP in the Canada Basin is closely associated with ice melting stages (Ouyang et al., 2021). Therefore, instead of using monthly averaged NCP, we incorporated NCP estimation based on the relationship between ice concentration and NCP into our model.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, summer stratification strengthens its oligotrophic characteristics (Ardyna & Arrigo, 2020; Ji et al., 2019). Interestingly, a recent study further found that NCP in the Canada Basin is closely associated with ice melting stages (Ouyang et al., 2021). Therefore, instead of using monthly averaged NCP, we incorporated NCP estimation based on the relationship between ice concentration and NCP into our model.…”
Section: Methodsmentioning
confidence: 96%
“…Briefly, NCP (5.6 ± 2.0 mmol C m −2 d −1 ) was relatively high during the actively melting period (ice% from 30% to 50%), whereas NCP (1–2 mmol C m −2 d −1 ) was lower in the pre‐melt (ice% >80%) and post‐melt period (ice% <15%) (Figure S2 in Supporting Information S1). This relationship was established by examining the histories of wind and ice in a given location combined with the underway measurement of Δ(O 2 /Ar) (Ouyang et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…As described in Supporting Text S1, the majority of gas transfer velocities we derived from instantaneous or monthly-averaged wind speeds were systematically biased low compared to mixed layer residence time-weighted sea-air fluxes (Wanninkhof et al, 2002(Wanninkhof et al, , 2009. In addition, sea ice decreases the effective gas transfer velocity, and it is thus necessary to incorporate ice cover variability prior to sampling to accurately calculate the timeweighted sea-air flux (Ji et al, 2019;Ouyang et al, 2021).…”
Section: Sea-air Flux Calculationsmentioning
confidence: 99%
“…These blooms consume dissolved inorganic carbon (DIC) in the upper water layer, resulting in a lower pCO 2 level of the sea surface (<100-350 μatm) compared to that of the atmosphere (Bates, 2006). During the ice-free period, the mean air-sea CO 2 flux over the entire Chukchi Sea typically ranges from −10 mmol m −2 d −1 to −40 mmol m −2 d −1 (Bates, 2006;Evans et al, 2015;Gao et al, 2012;Murata & Takizawa, 2003;Ouyang et al, 2021;Pipko et al, 2002Pipko et al, , 2015Semiletov et al, 2007;Wang et al, 2003), with some low extremes of less than −70 mmol m −2 d −1 around the Hanna Shoal and Barrow Canyon vicinity (Bates, 2006;Mathis & Questel, 2013). Juranek et al (2019) concluded that biological production plays an important role in maintaining an oceanic carbon sink in the eastern Chukchi Sea during October 2011 and 2012.…”
mentioning
confidence: 99%